Pengaruh Minat dan Motivasi Belajar Terhadap Hasil Belajar Semua Mata Pelajaran Peserta Didik Program Paket C di SKB Negeri Surabaya - Elok, Anjeli Mifta; Soedjarwo, Soedjarwo (J+PLUS UNESA, 2024)
This research aims to determine: The influence of motivation and interest in learning on the learning outcomes of all subjects of students in the package C equal education program at SKBN Surabaya. SKB Negeri Surabaya is a package C equality education program organized by the Surabaya city government, with a workforce of 10 people and 46 students. The process of implementing learning at SKB Negeri Surabaya uses modules provided by the Ministry of Education and Culture, where learning at SKB Negeri Surabaya focuses on the learning process for students, so that it can produce satisfactory learning outcomes. The learning outcomes obtained by students will of course also be different from each other because there are many influencing factors. This research is a quantitative approach research. The subjects of this research are all students of Class X SKB Negeri Surabaya for the 2022/2023 academic year, totaling 30 students. The data collection technique uses a questionnaire distributed to research respondents with a study population of 30 students and documentation. The data analysis technique uses multiple regression analysis to answer the research questions.